PENTINGNYA KEBENARAN ALLAH SEBAGAI LANDASAN PENDIDIKAN KRISTEN [THE SIGNIFICANCE OF GOD’S TRUTH AS THE FOUNDATION OF CHRISTIAN EDUCATION] - Tarigan, Musa Sinar (JOHME: Journal of Holistic Mathematics Education, 2019)
Christian education plays a very significant role in guiding a person in true knowledge and the work of the Triune God as stated in the Bible. The righteousness of God centered on Christ will underlie all human life as God's glorious creation. God's truth will guide every believer to teach the principle of knowing God through education. This responsibility is very important as Christian education is facing various challenges of the times that are not faithful to the Bible. The learning process carried out only fulfills the cognitive aspect or renewal of character in general and does not touch the source of knowledge, that is, the true God. As a result, students understand learning based on personal ability and experience but do not recognize the main source, namely God himself. This research aims to explore Bible principles as the foundational basis of Christian education. To achieve these objectives, this research uses literary research by examining various educational problems faced by Christians, various phenomena of the learning process that occur through various writings by experts in education and relevant theological fields. Some texts in the Bible will be examined according to the framework of reformed theology and related to the field of Christian education. This research shows that Christian education leads students to know God, experience renewal of life in Christ, and understand that God is the source of knowledge. Therefore, Christian education must be based on God's truth in the Bible.BAHASA INDONESIA ABSTRAK: Pendidikan Kristen memiliki peran yang sangat signifikan untuk menuntun pengenalan yang benar akan pribadi dan karya Allah Tritunggal sebagaimana dinyatakan di dalam Alkitab. Kebenaran Allah yang berpusat kepada Kristus akan mendasari segala kehidupan manusia sebagai ciptaan Tuhan yang mulia. Kebenaran Allah akan menuntun setiap orang percaya untuk mengajarkan prinsip pengenalan akan Allah melalui pendidikan. Tanggung jawab ini begitu penting mengingat pengembangan pendidikan Kristen menghadapi berbagai tantangan zaman yang tidak setia dengan Alkitab. Proses pembelajaran yang dilakukan hanya memenuhi aspek kognitif atau pembaharuan karakter secara umum dan tidak menyentuh sumber pengetahuan tersebut yaitu Allah sejati. Akibatnya peserta didik memahami pembelajaran berdasarkan kemampuan dan pengalaman pribadi, tetapi tidak mengenali sumber utamanya yaitu Allah sendiri. Penelitian ini bertujuan untuk menggali prinsip Alkitab sebagai dasar-dasar pendidikan Kristen. Untuk mencapai tujuan tersebut, penelitian ini menggunakan riset literatur dengan meneliti berbagai permasalahan pendidikan yang dihadapi oleh orang Kristen, dan berbagai fenomena proses pembelajaran yang terjadi melalui berbagai tulisan para ahli bidang pendidikan dan bidang teologi yang relevan. Beberapa teks dalam Alkitab akan dikaji berdasarkan kerangka teologi reformed dan dihubungkan dengan bidang pendidikan Kristen. Penelitian ini menunjukkan bahwa pendidikan Kristen menuntun siswa mengenal Allah, mengalami pembaharuan hidup di dalam Kristus, dan memahami bahwa ilmu pengetahuan bersumber dari Allah. Oleh karena itu, pendidikan Kristen harus berdasarkan kebenaran Allah dalam Alkitab.